PELAKSANAAN LAYANAN KONSELING KELOMPOK TEKNIK KONTRAK PERILAKU DALAM MEREDUKSI PERILAKU AGRESIF PADA SISWA SMP DI SAMARINDA TAHUN AJARAN 2024/2025 - Husnul Khotimah; Wahyu Widyatmoko (FOKUS : Kajian Bimbingan dan Konseling dalam Pendidikan, 2026)
This study aims to determine the level of student aggression after providing group counseling services with behavior contract techniques. The research design used was action research in guidance and counseling (PTBK) consisting of 2 cycles and each cycle consists of 4 stages, namely planning, action, observation, and reflection. The sample in this study amounted to 5 students selected using purposive sampling. Data collection using psychological scales of aggressive behavior, interviews, observation, and documentation. The results of the initial assessment analysis using a psychological scale before being given group counseling services with behavior contract techniques showed an average score of 97.4 including in the high category while the results of the assessment analysis after the provision of behavior contract group counseling services cycle 2 showed an average score of 75.8 including in the low category. Based on the results of interviews and observations that have been made, there are changes after being given behavior contract counseling services where aggressive behavior by students has begun to decrease. This research is expected to be an input for strategies in reducing aggressive behavior for further research.